Children and Exercise XXVI : the Proceedings of the XXVIIth International Symposium of the European Group of Paediatric Work Physiology, September, 2011. - Armstrong, Neil (Taylor & Francis, 2011)
Children and Exercise XXVII presents the latest scientific research into paediatric sport and exercise science and medicine, including contributions from a wide range of leading international experts and early career researchers. The book begins with chapters devoted to the five invited keynote lectures, followed by forty-two of the peer-reviewed presentations which are arranged into five thematic sections addressing: exercise physiology physical activity and health exercise and medicine testing and performance young athlete and sports participation. The forty-seven chapters offer a review of.